Assessing Computer Skills and attitudes toward electronic learing and internet use in a sample of third year medical students of baghdad medical college- iraq. - Al naaimi, Ahmed. S. (Journal of the Faculty of Medicine Baghdad, 2011)
introduction: medical schools and medical education look different as we advance into the 21st century. The call for medical students to become literate in the uses of information technology has become a familiar reform.